2017
DOI: 10.1177/2332858417706899
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of a Kindergarten Mathematics Intervention by Small Group Size

Abstract: This study used a randomized controlled trial design to investigate the ROOTS curriculum, a 50-lesson kindergarten mathematics intervention. Ten ROOTS-eligible students per classroom (n = 60) were randomly assigned to one of three conditions: a ROOTS five-student group, a ROOTS two-student group, and a no-treatment control group. Two primary research questions were investigated as part of this study: What was the overall impact of the treatment (the ROOTS intervention) as compared with the control (business as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 71 publications
8
50
0
Order By: Relevance
“…Findings from two of the studies indicated that aggregated treatment students in the 2:1 ROOTS and 5:1 ROOTS groups significantly outperformed their control condition peers on a host of standardized mathematics achievement measures, with reported effect sizes (Hedges’s g ) ranging from .12 to .95 (Clarke et al, 2016; Doabler et al, 2016). In two other studies that examined the effect of group size on intervention impact, nonsignificant differences between the 2:1 ROOTS and 5:1 ROOTS groups were found, suggesting that the impact of ROOTS was essentially the same regardless of group size (Clarke et al, 2017; Doabler et al, 2019). Whereas the collective results of this research program were encouraging, they in turn raised questions as to why ROOTS has led to increased student mathematics achievement in different instructional formats (2:1 and 5:1 group sizes) for a range of at-risk learners from different geographical regions of the United States.…”
Section: Tier 2 Kindergarten Mathematics Intervention Researchmentioning
confidence: 91%
“…Findings from two of the studies indicated that aggregated treatment students in the 2:1 ROOTS and 5:1 ROOTS groups significantly outperformed their control condition peers on a host of standardized mathematics achievement measures, with reported effect sizes (Hedges’s g ) ranging from .12 to .95 (Clarke et al, 2016; Doabler et al, 2016). In two other studies that examined the effect of group size on intervention impact, nonsignificant differences between the 2:1 ROOTS and 5:1 ROOTS groups were found, suggesting that the impact of ROOTS was essentially the same regardless of group size (Clarke et al, 2017; Doabler et al, 2019). Whereas the collective results of this research program were encouraging, they in turn raised questions as to why ROOTS has led to increased student mathematics achievement in different instructional formats (2:1 and 5:1 group sizes) for a range of at-risk learners from different geographical regions of the United States.…”
Section: Tier 2 Kindergarten Mathematics Intervention Researchmentioning
confidence: 91%
“…One question that is beginning to receive some recent attention in the intervention literature is; what is the optimal size for an intervention group? (e.g., Clarke et al, 2017;Vaughn, Thompson, Kouzekanani, & Dickson, 2003). Within the reading intervention literature, Vaughn et al (2003) found that a ratio of one educator to three students (1:3) had a significant impact on student reading performance that was indistinguishable from the same intervention that employed a 1:1 ratio.…”
Section: The Social-cognitive Rationale: Principlementioning
confidence: 99%
“…The question arises as to why it is the case that small group interventions appear equally effective as individualized interventions, given that the intensity of an intervention can be assumed to decline for every additional individual that is added to the group,. One explanation put forward by Clarke et al (2017) is the presence of a threshold effect; suggesting that practicing desired behaviors beyond a certain point is largely redundant. However, an alternative explanation relates to the observation that students learn mathematics through opportunities to construct their understanding in a social context, such as through peer-to-peer interactions (Kieran, 2001;Pijls, Dekker, & Van Hout-Wolters, 2007;Zakaria, Chin, & Daud, 2010).…”
Section: The Social-cognitive Rationale: Principlementioning
confidence: 99%
“…To implement number line board games requires only minimal training time, costs (i.e., materials), and prerequisite mathematics skills (e.g., Ramani, Siegler, & Hitti, 2012). Considering these accessible requirements, the ease of implementation may allow nonteachers such as older students (i.e., cross-age tutors) to deliver the intervention, with high levels of fidelity, allowing for teachers to arrange smaller instructional groupings of students in need of individualized, explicit instruction (Clarke et al, 2017; Doabler et al, 2017).…”
mentioning
confidence: 99%